2017
DOI: 10.1016/j.ejpal.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Structured behavioral interview as a legal guarantee for ensuring equal employment opportunities for women: A meta-analysis

Abstract: Equal employment opportunities for women are a legal requirement in many legal environments, including the United States (US) and European Union (EU) legislations. In this context, indirect discrimination in the access to jobs is an illegal practice. For this reason, personnel selection procedures must be fair for protected-by-law groups. Specifically, gender discrimination is the focus of research on employment interviews. This article presents a meta-analysis of gender differences in the scores in structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…Other relevant studies have found that the SBI is more resistant to adverse impact (Alonso, 2011;Alonso, Moscoso, & Salgado, 2017;Levashina, Hartwell, Morgeson, & Campion, 2014;Rodríguez, 2016). There is also evidence of the economic utility of the SBI (Salgado, 2007).…”
Section: Employment Interviews: Types and Psychometric Propertiesmentioning
confidence: 94%
“…Other relevant studies have found that the SBI is more resistant to adverse impact (Alonso, 2011;Alonso, Moscoso, & Salgado, 2017;Levashina, Hartwell, Morgeson, & Campion, 2014;Rodríguez, 2016). There is also evidence of the economic utility of the SBI (Salgado, 2007).…”
Section: Employment Interviews: Types and Psychometric Propertiesmentioning
confidence: 94%
“…For example, the family of Pearson correlation coefficients is widely used in validity studies in work and organizational (W/O) psychology (e.g., Lado & Alonso, 2017;Rodríguez, 2016) and in psychometric meta-analytic methods and validity generalization studies (Salgado, 2017;Salgado, Moscoso, & Anderson, 2016;Schmidt & Hunter, 2015). Cohen's d is the most common ES in experimental studies, for estimating the utility of clinical interventions (e.g., the effects of psychotherapy), in the Glassian meta-analytic method (Glass, 1976;Glass, McGraw, & Smith, 1981), and in the study of gender differences (e.g., Alonso, Moscoso, & Salgado, 2017). Fisher's Z transformation of correlation coefficients is used extensively in the study of attitudes and is the basis of the correlational meta-analysis method developed by Hedges and Olkin (1985).…”
Section: Palabras Clavementioning
confidence: 99%
“…Additionally, the conclusions of several primary studies about other important implications of the use of different types of interview (for example, their resistance to bias, the degree to which interviewers feel confident about their decisions, the probability of their producing adverse impact, their economic utility, etc. ), also recommended the use of the most structured ones (Alonso, 2011;Alonso, Moscoso, & Salgado, 2017;Rodríguez, 2016;Salgado, 2007).…”
Section: Applicants' Perception Of Different Types Of Interviewsmentioning
confidence: 99%